184 Evaluation of Aviplus on Growth Performance of Nursery and Growing-finishing Pigs. (7th May 2021) - Hutchens, Wade M; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Calderon, Hilda I; Keppy, Kaylee; Stephens, Kevin; Maynard, Philip
Abstract: A total of 1, 215 pigs (L337×1050, PIC, Hendersonville, TN) were used in a 156-d wean-to-finish experiment. Pigs were weaned at 21 d of age and placed in pens based on initial body weight (BW) with 27 pigs/pen. There were three dietary treatments including a: 1) control; 2) pigs fed diets containing AviPlus (micro-encapsulated sorbic and citric acids and synthetic thymol and vanillin botanicals; Vetagro Inc., Chicago, IL) during the nursery and finisher phases; or 3) pigs fed AviPlus during the nursery but not the finishing phase. AviPlus was included at 2.72 kg/ton from d 0 to 21, 0.90 kg/ton from d 21 to 42, and 0.45 kg/ton from d 42 to 156. Thus, there were 15 control pens and 30 Aviplus pens in the nursery and 15 pens for the 3 treatments in the finisher phase. On d 42, pigs were transported as intact pens to the finishing facility. Data were analyzed as a RCBD with pen as experimental unit. For the overall nursery period (d 0 to 42), pigs fed AviPlus had improved (P < 0.05) G:F, with no evidence of difference (P > 0.05) for d 42 BW, ADG, or ADFI. For the overall finishing period (d 42 to 156) and overall experimental period (d 0 to 156), there was no evidence of difference (P > 0.05) for BW, ADG, ADFI, or G:F. There was no evidence of difference (P > 0.05) observed for mortality and removals during the nursery, finisher, or overall. In summary, providing AviPlus during the nursery improved nursery G:F, but there was no effect on overall wean-to-finish performance.